Environmental control of macrophyte traits and interactions with metabolism and hydromorphology in a groundwater‐fed river. (13th September 2020) - Reitsema, Rosanne E.; Preiner, Stefan; Meire, Patrick; Hein, Thomas; Dai, Yanran; Schoelynck, Jonas
Abstract: Macrophytes are important organisms in running water systems, having a decisive role in ecological processes and interactions. Their temporal and spatial distribution in streams can be highly variable, and this is often determined by flow velocity. In this study, macrophyte growth, morphology and nutrient stoichiometry were studied monthly during one growing season in reaches with different flow velocity and flow velocity distribution and, as a result, different distributional plant patterns in an Austrian lowland stream, dominated by evergreen macrophyte species, Berula erecta . Flow velocity, water depth, fine sediment layer depth and metabolism were measured in the stream and the correlation with plant biomass and morphological traits was tested. We aimed to study differences between reaches with different distributional plant patterns and whether common interactions between macrophytes and flow velocity can also be observed when vegetation is evergreen. Plant biomass showed seasonal variation, with the highest values in June and the lowest in February. In the reach with low flow velocity and homogeneous macrophyte distribution, biomass peaked in summer and plant morphology changed with the seasons, whereas biomass and morphology in the reach with high flow velocity and patchy distribution were more constant throughout the year. Plant carbon, nitrogen and phosphorus content were higher in spring and autumn than in summer, whereas biogenic silica accumulated over the course of the growth season. Stream metabolism was strongly correlated with macrophyte biomass, and this correlation was stronger in the reach with homogeneous macrophyte distribution than in the reach with a patchy distribution. Moreover, average leaf area and stem length were positively correlated with fine sediment layer depth, and negatively with flow velocity. The results stress the importance of macrophyte growth and morphology in river processes like metabolism, hydromorphology and nutrient dynamics: especially plant morphology plays an important role in macrophyte–flow interactions.